2016
DOI: 10.1016/j.jece.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A review on Fenton-like processes for organic wastewater treatment

Abstract: Fenton-like processes have been studied widely in recent years and are considered promising for organic wastewater treatment. Due to the demand for high efficiency wastewater treatment, a summary of the study status of Fenton-like processes is necessary to develop a novel and high efficiency organic wastewater treatment method. In this review, some important effect parameters (pH, H2O2 dosage, catalyst dosage, temperature) in hetero-/homo-geneous Fenton-like processes are discussed, and then the physical field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
299
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 766 publications
(313 citation statements)
references
References 213 publications
(279 reference statements)
4
299
1
9
Order By: Relevance
“…Fenton process perform better at lower pH since the production of hydroxyl radicals is influenced by pH (Qiao et al, 2005). Result from the experiment is similar to a review reported by Wang et al (2016). Figure 3 illustrates the effect of pH in fenton process and ozonation.…”
Section: Results and Discussion Effect Of Phsupporting
confidence: 80%
“…Fenton process perform better at lower pH since the production of hydroxyl radicals is influenced by pH (Qiao et al, 2005). Result from the experiment is similar to a review reported by Wang et al (2016). Figure 3 illustrates the effect of pH in fenton process and ozonation.…”
Section: Results and Discussion Effect Of Phsupporting
confidence: 80%
“…This process shows obvious advantages on oxidizing recalcitrant substances, and it is usually used as pretreatment process to increase the biodegradability of the wastewater by increasing the B/C value [6][7][8]. However, it also shows some inevitable drawbacks mainly in formation of ferric hydroxide sludge above pH 4.0 [9], and difficulty in catalyst recovery from the sludge.…”
Section: Introductionmentioning
confidence: 99%
“…The process is also fast, effective and capable of degrading harmful, toxic and non-biodegradable compound in the wastewater through the oxidation process [5]. The Fenton reagents involve the application of ferrous ions (Fe 2+ ) to react with hydrogen peroxide (H 2 O 2 ) producing hydroxyl radicals (OH • ) with the powerful oxidizing ability to degrade organic pollutants in wastewater [6] otherwise there is no energy needed in terms of activating hydrogen peroxide because the reaction takes place at room temperature and atmospheric pressure [7].…”
Section: Introductionmentioning
confidence: 99%